The Effect of Coffee Fruit Skin Extract on Sperm Characteristics And Testicular of Mice With Ethanol-Induced - Haris Setiawan; Rita Maliza; Syaiful Adam Maulana; Muhammad Ilham Hisbullah (UIN Sunan Gunung Djati Bandung, 2020)
Coffee fruit skin contains antioxidant compounds that can repair damaged tissues, especially those of reproductive or-gans. This study was designed to assess to what extent the metha-nolic extract of coffee fruit skin affected sperm characteristics and testicular histology in mice receiving 15% ethanol for 15 days. It used 25 male mice aged four months and employed a completely randomized design with two controls (K) and three treatments (P), namely K1 (without ethanol), K2 (15% ethanol), P1 (15% ethanol and the methanolic extract of coffee fruit skin, or MECS, at 125 mg/ kg BW), P2 (15% ethanol and MECS 250 mg/kg BW), and P3 (15% ethanol and MECS 500 mg/kg BW). These treatments were administered orally with a 1 mL disposable syringe for 15 days. The parameters observed were sperm characteristics (viability, morphology, and sperm count) and the microscopic structure of the testicles (lu-men area, diameter, and area of seminiferous tubules). These data were then analyzed using the one-way ANOVA, continued with the LSD and Duncan’s tests (P <0.05). The results showed that P2 (250 mg/kg BW) substantially improved sperm count (86.5x105±1.73 cells/ mL), sperm viability (87.26±0.05%), and the proportion of normal sperm morphology (93.33±0.004%) of mice with 15% ethanol-in-duced sperm damages. Testicular histology also confirmed improve-ments in spermatogenic cells, as evident from the lumen, diameter, and area seminiferous tubules after receiving P1 and P2. In conclu-sion, the optimum dose of the coffee skin extract for improving sperm quality and microscopic structures of mice testicles is 250 mg/kg BW.